Usia Perkawinan Perspektif Maqashid Syariah; Analisis terhadap Undang-Undang Perkawinan di Indonesia - Baharuddin, Hendrah; Sastrawati, Nila (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2021)
The objectives of this study are to: 1)What is the background of the change in Article 7 paragraph (1) of Law Number 1 of 1974 to Law Number 16 of 2019, 2) how does Maqashid al-Syari’ah review changes to Article 7 paragraph (1) of Law Number 1 Year 1974 became Law Number 16 of 2019. In answering these problems, the researchers used the syar’i normative method. This study uses a library research method. Furthermore, the data collection method that the writer uses is direct cutifan, namely the researcher directs a person’s opinion or writing according to the original without changing it and indirect quotations, namely quoting other people’s writings, data and opinions by formulating with a new arrangement, but with the same intention. The results of this study indicate that the minimum age limit of marriage in Article 7 paragraph (1) of the Marriage Law has changed quite well which is in Law no. 1 of 1974 put a minimum age of marriage, namely 16 years for women and 19 years for men, is currently being amended in Article 7 paragraph 1, where the minimum age of marriage for women and men is at the same level, namely at least 19 years to be able to get married. In the review of maqashid al-sharia, the minimum limit in marriage is not explicitly regulated, but as long as it concerns the benefit of the ummah, it can be used in the administration of marriage. The implications of this study regarding changes in the minimum age limit for marriage in Article 7 paragraph 1 of the Marriage Law are expected to be able to be implemented properly by parties, both organizers, parents and men and women, should pay attention to various aspects before carrying out a marriage so that the marriage dreams can come true and do not end in an unwanted divorce. KeyWords: Constitution, marriage, Maqashid Al-Syari’ah